Penggelapan Pajak Bea Perolehan Hak Atas Tanah dan Bangunan Oleh Pejabat Pembuat Akta Tanah Pembuatan Akta Jual Beli - Arina Husnawati; Adnan Hamid; Tetti Samosir (CV Rewang Rencang, 2025)
The role of PPAT in land registration is to assist the Head of the Land Office to carry out certain activities in land registration, one of which is by facilitating and assisting taxpayers in paying BPHTB. The problem in this thesis is regarding the authority of PPAT in managing the payment of BPHTB tax fees in the transfer of land rights and the actions of PPAT in embezzling BPHTB tax fees which is detrimental to state finances in Decision Number 474/Pid.B/2021/PN.Bks. This thesis, using normative legal research methods (library) with qualitative analysis of secondary data to obtain conclusions about the authority of PPAT in managing the payment of BPHTB tax fees in the transfer of land rights is not regulated in laws and regulations, so it is not the authority of PPAT to make payments of BPHTB tax fees. However, because the PPAT has received the deposit of BPHTB tax fees from his client, the PPAT must be responsible in his position to deposit the BPHTB tax fees, this deposit of BPHTB tax fees is carried out because he has been trusted by his client. The actions of PPAT in embezzling BPHTB tax fees which is detrimental to state finances in Decision Number 474/Pid.B/2021/PN.Bks, namely the PPAT can be held criminally responsible for committing a criminal act of embezzlement, civil there is a loss to another person and the PPAT PP and the code of ethics and committing a violation of Article 26 paragraph (1) of the BPHTB Law and Article 6 of the PPAT Code of Ethics.